2004
DOI: 10.2169/internalmedicine.43.919
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum C-reactive Protein Levels and Microalbuminuria: A Population-Based Cross-Sectional Study in Northern Iwate, Japan

Abstract: Objective The presence of microalbuminuria is a renal marker of vascular endothelial damage, and is an independent and strong predictor of increased risk for cardiovascular mortality and morbidity. Elevated circulating C-reactive protein (CRP) levels have recently been reported to be a novel cardiovascular risk factor, and it has been suggested that this acute-phase protein impairs vascular endothelial function. The aim of the present study was to determine whether serum CRP level is a dependent or an independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 38 publications
8
34
2
Order By: Relevance
“…Thus, the present data may not accurately reflect the characteristics of the general population. In fact, the frequency of microalbuminuria in this study (5.5%) was much lower than that of the other Japanese general populations such as those of Iwate Kenpoku (19%) 26 and Takahata (14%). 27 People who participate in regular health checkups are normally healthier and have better prognosis than people who do not.…”
Section: Risk Of Microalbuminuria M Munakata Et Alcontrasting
confidence: 75%
“…Thus, the present data may not accurately reflect the characteristics of the general population. In fact, the frequency of microalbuminuria in this study (5.5%) was much lower than that of the other Japanese general populations such as those of Iwate Kenpoku (19%) 26 and Takahata (14%). 27 People who participate in regular health checkups are normally healthier and have better prognosis than people who do not.…”
Section: Risk Of Microalbuminuria M Munakata Et Alcontrasting
confidence: 75%
“…In the study of Palwasha Sahibzada et al [13,14] reported that total of 45.1% patients were with STEMI, from them 29% were anterior wall myocardial infarctions and 16% were inferior wall MI, 29% patients suffered NSTEMI and 29% were diagnosed as ACS. Similarly in this study on ECG and cardiac biomarkers findings 38% were noted with anteriolateral wall MI, 30.0% with inferior wall MI.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 We compared CVD risk factors and cardiovascular comorbid conditions in hemodialysis patients in the KAREN Study to those in the general population, as determined in the Iwate KENCO Study.…”
Section: Data Handling and Classificationmentioning
confidence: 99%